ANALYSIS OF FACTORS RELATED TO THE PERFORMANCE OF MIDWIFE IN FAMILY PLANNING COUNSELING SERVICES - NITA FARIDA; ARI KURNIASIH; RATUMAS RATIH PUSPITA (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACTCounseling is a process that runs and integrates with all aspects of family planning services and not just information that is given and discussed on one occasion, namely at the time of service delivery. Good counseling will help clients to use their contraception longer and increase the success of family planning. Often counseling is ignored and not carried out properly because the officers do not have the time and do not realize the importance of counseling. The general purpose of this study was to determine the factors related to the performance of midwives in family planning counseling services in the work area of the Karawang District Health Office. This research uses analytical method with cross sectional approach. The population in this study were all midwives who served in the Puskesmas working area of the Karawang Regency Health Office. The sample in this study was taken using the Lameshow formula so that the minimum number of samples was 115 respondents. The results of statistical tests of variables that have a significant relationship with the performance of midwives in family planning counseling services in the work area of the Karawang District Health Office are knowledge with a value of P = 0.000, length of work (p = 0.002), facilities and infrastructure with a value (p = 0.012), and training. (P = 0.001), while the variables that do not have a significant relationship are reward (p = 0.389), and superior support (p = 0.766). Keywords: Counseling, Midwife, Family Planning ABSTRAKKonseling adalah proses yang berjalan dan menyatu dengan semua aspek pelayanan keluarga berencana dan bukan hanya informasi yang diberikan dan dibicarakan pada satu kesempatan yakni pada saat pemberian pelayanan. Konseling yang baik akan membantu klien dalam menggunakan kontrasepsinya lebih lama dan meningkatkan keberhasilan KB. Seringkali konseling diabaikan dan tidak dilaksankan dengan baik karena petugas tidak mempunyai waktu dan tidak menyadari pentingnya konseling. Tujuan umum penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan kinerja bidan dalam pelayanan konseling KB diwilayah kerja Dinas Kesehatan Kabupaten Karawang. Penelitian menggunakan metode analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua bidan yang bertugas di Puskesmas wilayah kerja Dinas Kesehatan Kabupaten Karawang. Sampel dalam penelitian ini diambil dengan menggunakan rumus Lameshow sehingga jumlah sampel minimal yaitu 115 responden. Hasil ujistatistic variabel yangmempunyai hubungan yang bermakna dengan kinerja bidan dalam pelayanan konseling KB di wilayah kerja dinas kesehatan Kabupaten Karawang yaitu pengetahuan dengan nilai P=0,000, lama kerja (p= 0,002), sarana dan prasarana dengan nilai (p=0,012), dan pelatihan (P= 0,001),sedangkan variabel yang tidak memiliki hubungan yang bermakna adalah reward (p= 0,389), dan dukungan atasan (p = 0,766). Kata kunci: Bidan, Keluarga Berencana, Konseling